Análise dinâmica não-linear de lajes em concreto armado sob ação de cargas impulsivas provenientes de explosão: . - Wellington Antonio Soares (1991)
Criteria and prcedures for the dynamic non-linear analysis of retangular reinforced plates subjected to impulsive loads from explosions are presented in this work. Simple supports and clamped adges are the boundary conditions os the plates.First each plate transformed into a non-damped euivalent system with a single degree of freedon.The response of the equivalent system to the impulsive load is then computed based on the linear acceleration method.A PC microcomputer program is a powerful tool resulting fron this Work..With this software the user can perform a quick and low cost analysis of the plates covered in this thesis